Can hunter’s local ecological knowledge be used in management of multi-ungulate systems? : a combination of local ecological knowledge and scientific knowledge to add a finer resolution to current management strategies - Pettersson, Sandra (SLU/Dept. of Wildlife, Fish and Environmental Studies, 2021)
Management and conservation of wildlife populations are generally based on scientific knowledge (SK) and monitoring to establish reliable information. The information gathered and presented from SK is interpreted by individuals who can have different ways of interpreting the same type of information. To increase the validity and range of opinions, other types of knowledge can be incorporated with SK. There are a variety of non-scientific types of knowledge that can be used depending on the research question, such as local ecological knowledge (LEK), local knowledge (LK), traditional ecological knowledge (TEK) and indigenous local-, and traditional knowledge (ILK/ITK). Wildlife management in Sweden already uses alternative knowledge systems incorporated with SK in monitoring of ungulates. This monitoring is predominantly used for spatial distribution and population indices. In management of multi-ungulate systems, it can be beneficial to have monitoring and management measures done on a smaller and more local scale. This can be done with a combination of SK and LEK from hunters, who have an accumulated knowledge based on experience and observations over a lifetime. In this thesis, I investigate if LEK and SK can successfully be incorporated in management of multi-ungulate systems. First, I conduct a systematic review to explore how many studies have been analysing the overlap between LEK and SK regarding terrestrial mammals. Then I carried out a pilot study on Järnäs peninsula located in northern Sweden, where four different ungulate species are present, moose Alces alces, roe deer Capreolus capreolus, fallow deer Dama dama and red deer Cervus elaphus. For this, I use three different data sets: a questionnaire survey to establish LEK and for SK, camera traps for distribution, and DNA metabarcoding for diet data. I found that experience or age of hunters did not influence the LEK/SK overlap. The hunter estimates predict 30% of the DNA data, the diet deviated most for birch, Vaccinium, graminoids and “other”. ...